Women gender and discrimination - Hossain, Kazi Tobarak; Imam, Muhammad Hasan; Habib, Shah Ehsan; Rajshahi University. Higher Education Link Programme; Great Britain. Department for International Development, Bangladesh (Rajshahi : Higher Education Link Programme, Dept. of Sociology, University of Rajshahi, 2004)
Contributed papers presented at workshop on women and development and in a seminar on gender discrimination funded by Dept. of International Development, Bangladesh.
Includes bibliographical references.
Keywords: Women's rights -- Bangladesh -- Congresses; Women -- Bangladesh -- Social conditions -- Congresses